STUDIES ON INDUCTION OF OESTRUS IN LOCAL ANESTRUS COWS WITH PROGESTERONE PRIMED GnRH AND PROGESTERONE TREATMENT - PAWAR, S A; MARKANDEYA, N M; SAWALE, A G; KASBE, R D (The Indian Journal of Animal Reproduction, 2023)
The research experiment to study the efficacy of progesterone primed GnRH and progesterone protocol forinduction of oestrus in local anestrous cows were conducted in 54 local cows. In group I (n= 18), injection progesterone(250 mg) on day 1st followed by inj. GnRH (0.0105 mg) on day 10th 77.77 percent animals exhibited oestrus andafter insemination 84.61 per cent cows conceived with 1.50 services per conception, whereas in group ti (n = 18).of progesterone treatment, 61 .11 per cent cows showed exhi bitory oestrus and after insemination, 63 .63 per centconceived with 1. 71 services per conception as against control. The progesterone treatment response in terms ofoestrus induction, conceptio:1 pregnancy rate and cyclicity rate statistically differed with progesterone primedGnRH therapy.
Keywords: Fertility; Local cows; Oestrus; Progesterone; GnRH